Appetite during the second and third trimesters mediates the impact of prenatal environmental tobacco smoke exposure on symmetric full-term low birth weight. (2nd May 2020) - Huang, Lihua; Tian, Fu-Ying; Fan, Lijun; He, Yan-Hui; Peng, Ding; Xie, Chuanbo; Tao, Liu; Yuan, Shi-Xin; Jia, De-Qin; Chen, Wei-Qing
Abstract: Objective: To examine the relationship of prenatal environmental tobacco smoke (ETS) exposure and full-term low birth weight (FT-LBW) when taking anthropometric proportionality into consideration, and explore whether appetite mediates their association. Study design: We conducted a case-control study among pregnant women at two Women and Children's Hospitals in Guangdong, China. Information was collected through interview and medical records review. A series of logistic and linear regressions were used to examine the relationships of prenatal ETS exposure, appetite, and FT-LBW. Results: After adjusting for the potential confounders, prenatal ETS exposure was significantly negatively associated with FT-LBW (OR: 1.83, 95%CI: 1.35–2.48) and negatively correlated with maternal appetite in second and third trimester during pregnancy (β: −0.11, standard error: 0.03). Moreover, mediation analysis illustrated that maternal appetite partially mediated 12.00% of their relationship. However, subgroup analysis showed that prenatal ETS exposure was linked to higher risk of symmetric FT-LBW (OR: 2.26, 95%CI: 1.56–3.26) but not asymmetric FT-LBW. And maternal appetite explained only 6.45% of their relationship. Conclusions: Maternal prenatal ETS exposure increased risk of having symmetric FT-LBW infant, and appetite might mediate their relationship partially. This study emphasizes the importance of sample homogeneity and stresses the needs to improve the public awareness of the harmful effects of ETS.